Access to Finance for Women Entrepreneurs in Kenya: Challenges and Opportunities - Manwari, Louisa; Ngare, Philip; Kipsang, Rotuno (Scholarlink Research Institute, 2017)
This study investigated the challenges and opportunities affecting access to finance for women entrepreneurs in Kenya with the aim of making positive contributions to the Kenyan economic recovery strategies and policy contributions to the Women Enterprise Fund (WEF) by examining the crucial role that women entrepreneurs play in generating wealth and employment creation in the country. The challenges which were addressed included inadequate capital, lack of management & financial skills, inaccessibility to loans/credit, inadequate loan amount, lack of loan collateral, high taxation, inability/difficulty in repaying loans, increased competition, lack of training on business skills and low literacy levels. Using questionnaires and structured interviews to collect data, a correlation analysis on the variables, factor analysis followed by scale reliability tests were used to determine the validity of the results. Key among the recommendations on improving access to finance for women entrepreneurs is the use of mobile and ICT platforms to access loans from the Women Enterprise Fund. Women entrepreneurs need to use business support services like ICT to become more competitive and explore national and global value chains opportunities. The Women Enterprise fund needs to develop, through appropriate legislations, a funding model that uses mobile telephony for women entrepreneurs to access credit. The study findings are significant as they would enable the government to come up with appropriate legislative frameworks, a funding model and business support services that would improve access to finance for women entrepreneurs. This study concludes that the government should improve access to finance for women entrepreneurs, through strengthening friendly loan policies, regulations and use of ICT platforms like mobile telephony to provide loans. It is further concluded that the government through the Women Enterprise Fund should increase the number of loan holding banks to include SACCOs
Keywords: Women enterprise fund; Kenya; Challenges; Opportunity; Factor analysis; Scale reliability tests.